Understanding the pollutant molecular fate in a two-stage biological-coagulation-membrane distillation hybrid process for treating hypersaline organic wastewater - Wang, Ao; Xu, Hang; Yao, Chen; Hu, Tianlong; Wang, Jingjun; Lin, Tao; Tao, Hui; Ding, Mingmei (Desalination, 2025)
Membrane distillation (MD) is a promising technology for the reclamation of hypersaline organic wastewater due to its complete rejection of non-volatile compounds. In this study, a hybrid treatment process combining conventional biological treatment (two-stage activated sludge), coagulation–sedimentation, and MD was evaluated for achieving 80 % wastewater recovery. Experimental results showed that when flocculated effluent was used as the feed, stable MD performance was maintained over four consecutive running cycles without membrane cleaning, producing high-quality permeate with TDS of 8.76 ± 1.35 mg/L and COD of 1.29 ± 0.09 mg/L. To gain molecular-level insights into membrane fouling mechanisms, a non-targeted screening method based on two-dimensional gas chromatography–time-of-flight mass spectrometry was coupled with traditional water quality analysis and surface characterization. The results revealed that polar compounds, such as carboxylic acids, alcohols, and amides, tended to remain dissolved in the aqueous phase rather than contributing directly to membrane fouling. In contrast, membrane foulants were predominantly composed of low-polarity and structurally stable compounds that adsorbed and enriched on the hydrophobic membrane surface. Comparative analysis identified five key structural classes of dissolved organic matter that were most prone to accumulation and fouling: aliphatic saturated hydrocarbons, aliphatic esters, aromatic esters, oxygen-containing heterocycles, and nitrogen-containing heterocycles. This work provides a comprehensive understanding of pollutant fate and membrane fouling behavior in a two-stage biological–coagulation–MD hybrid system, offering practical implications for optimizing pretreatment strategies and improving the operational stability of MD in hypersaline wastewater reuse. [Display omitted] •A hybrid biological–coagulation–MD process achieved 80 % wastewater reuse;•GC × GC-TOFMS enabled molecular-level identification of membrane foulants;•Polar organics such as acids and alcohols were largely enriched in the feed;•Nonpolar species such as esters and heterocycles dominated membrane fouling.